2020
DOI: 10.1002/jlb.2hi0520-191r
|View full text |Cite
|
Sign up to set email alerts
|

Frontline Science: P2Y11 receptors support T cell activation by directing mitochondrial trafficking to the immune synapse

Abstract: T cells form an immune synapse (IS) with antigen-presenting cells (APCs) to detect antigens that match their TCR. Mitochondria, pannexin-1 (panx1) channels, and P2X4 receptors congregate at the IS where mitochondria produce the ATP that panx1 channels release in order to stimulate P2X4 receptors. P2X4 receptor stimulation causes cellular Ca 2+ influx that up-regulates mitochondrial metabolism and localized ATP production at the IS. Here we show that P2Y11 receptors are essential players that sustain these T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 67 publications
(156 reference statements)
1
11
1
Order By: Relevance
“…In neurons, cAMP promotes directional movement of mitochondria along the microtubule network ( 79 82 ), while local cytosolic Ca 2+ hotspots act as mitochondrial stop signals ( 83 ). Our recent work has shown that P2Y11 receptors promote trafficking of mitochondria to the IS of T cells ( 84 ). Thus, P2Y11 and P2X4 receptors jointly recruit and activate mitochondria at the IS in order to sustain T cell activation.…”
Section: P2y11 and P2x4 Receptors Orchestrate The Accumulation And Acmentioning
confidence: 99%
“…In neurons, cAMP promotes directional movement of mitochondria along the microtubule network ( 79 82 ), while local cytosolic Ca 2+ hotspots act as mitochondrial stop signals ( 83 ). Our recent work has shown that P2Y11 receptors promote trafficking of mitochondria to the IS of T cells ( 84 ). Thus, P2Y11 and P2X4 receptors jointly recruit and activate mitochondria at the IS in order to sustain T cell activation.…”
Section: P2y11 and P2x4 Receptors Orchestrate The Accumulation And Acmentioning
confidence: 99%
“…P2X1R and P2X4R trigger a localized Ca 2+ influx that stimulates OXPHOS and propagates TCR-induced signalling, culminating in cytokine secretion and T-cell proliferation [ 86 ]. Junger and co-workers recently showed that mitochondrial trafficking to the immune synapse is directed by P2Y 11 Rs [ 87 ], suggesting that these receptors cooperate with P2X4Rs to recruit and stimulate mitochondria at the IS. P2X4Rs and P2Y 11 Rs fulfil similar roles in promoting T-cell migration.…”
Section: P2 Receptors In T-cell Signalling and Metabolic Regulationmentioning
confidence: 99%
“…Together with the involvement of other interconnected organelles, mitochondria activated the cyclic guanosine monophosphate synthetase (cGAS)-stimulator of interferon genes (STING) signaling pathway, leading to the production of host defense type I IFNs and pro-inflammatory cytokines (211). Therefore, beyond producing the ATP that was released and necessary for driving systemic inflammation (39), mitochondria interacted with P2X1, P2X4 and P2Y 11 receptors to regulate T cell metabolism (212), migration (213) and activation (214); emphasizing the important role of purinergic signalling pathways in persistent neuroinflammation (215).…”
Section: Purinergic Targets For Sars-cov-2 Induced Pathologiesmentioning
confidence: 99%